K-State Turfgrass Research 2000 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2000)
This publication contains results of projects done throughout 1999 by K-State turfgrass researchers. You can see many of these projects in progress on August 3, 2000 at the Kansas Turfgrass Field Day. This will be held at the Rocky Ford Turfgrass Research Center in Manhattan. What questions can we answer for you? Maybe you're curious about the best performing tall fescue cultivars for lawns, bermudagrasses for fairways, or bentgrasses for greens. If you need to know how to manage fungicide programs to control diseases on tall fescue lawns or bentgrass greens, that information is here. As a superintendent, maybe you're having trouble keeping your putting greens in playable condition all summer - some suggestions lie inside. Keep this research report handy - it can be useful all year long. We also make this information available on our web site at : http:www.oznet.ksu.edu/dp_hfrr/welcome.htm. As always, we're interested in hearing your ideas about future research projects. This year marks the 50th anniversary of the Kansas Turfgrass Foundation. Plans are underway to help celebrate this milestone during the annual Turfgrass Conference in Topeka November 28- 30.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 855; Kansas Agricultural Experiment Station contribution; no. 00-423-S; Turfgrass; Pest management; Fescue; Bentgrass; Bluegrass; Zoysiagrass; Buffalograss